Fish Passage Facilities Design Parameters for Connecticut River Basin: Rainbow Dam, Farmington River, Windsor, Connecticut - Rizzo, B (ScholarWorks@UMass Amherst, 1972)
The purpose of this report is to provide guidelines regarding engineering design parameters and functional design features for proposed anadromous fish passage facilities at the Rainbow Dam on the Farmington River in Windsor, Connecticut. The anadromous fish species of main concern are American shad and Atlantic salmon.